(3GdcTGa Yf MbGFb GdJfRjd hYjhf GdCbGhjd aj hLhg GdJChjds - (3GdnqRnerNnTpQj GdNhGQRej, CHh GdbGSe, LGQ Gddg, eMehO Hf YeQ Hf eMeO Hf CMeO, (B538 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B... (3GNJUe Edi CYQGHjGf aj HFQ abGd CMOgeG CfG aWQJgG (B.. (3GHJOGFgG hbQF GdPj aWQ GdSeGhGJ hGdCQV hLYd GdedGFcI hbQF LGYd GdedGFcI (B...s
(3BNQgG (B:s
.. (3ceG bQA ef MjK CaGV GdfGS Ke jHjf HGdLfI hGdfGS dCf GdKbdjf geG GdfhYGf GdehUhaGf (B.. (3Mb Gddg YR hLd Yf QShd Gddg Udi Gddg Ydjg dbO CfRdJ Ydj ShQJGf eG CfRd eKdgeG hEfc df JbQC ShQJjf CMH hdG CQVi YfO Gddg efgeGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\178s
(3cTa GdXfhf (B2\1475s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs